A potential contribution of decreased serum galectin‐10 levels to systemic inflammation and pulmonary vascular involvement in systemic sclerosis. Issue 7 (14th March 2021) - Awaji, Kentaro; Miyagawa, Takuya; Fukui, Yuki; Toyama, Satoshi; Omatsu, Jun; Norimatsu, Yuta; Ikawa, Tetsuya; Watanabe, Yusuke; Yoshizaki, Ayumi; Sato, Shinichi; Asano, Yoshihide
Abstract: Objective: Galectin‐10 (Gal‐10) is a key molecule involved in eosinophil‐mediated suppression of T‐cell immune response. Systemic sclerosis (SSc) is characterized by T helper (Th) 2/Th17 immune response and impaired function of regulatory T cells, but the pathological role of Gal‐10 has not been studied so far. Therefore, we investigated the clinical correlation of serum Gal‐10 levels in SSc patients. Methods: Serum Gal‐10 levels were determined by enzyme‐linked immunosorbent assay in 38 patients with diffuse cutaneous SSc (dcSSc), 30 with limited cutaneous SSc and 20 healthy controls. Clinical correlations of serum Gal‐10 levels were examined. Results: Serum Gal‐10 levels were significantly lower in SSc patients than in healthy controls, especially in dcSSc patients, and inversely correlated with skin score, the percentage of predicted diffusion lung capacity for carbon monoxide and estimated right ventricular systolic pressure (RVSP). Furthermore, serum Gal‐10 levels had negative correlations with leucocyte counts and inflammatory parameters. Multivariate regression analysis identified C‐reactive protein and RVSP as explanatory parameters for serum Gal‐10 levels. Conclusion: Decreased serum Gal‐10 levels may reflect the impairment of eosinophil‐mediated regulatory system for T‐cell immune response in SSc, possibly contributing to pulmonary vascular involvement leading to pulmonary arterial hypertension.